Customer relationship management in the digital age - Shainesh, G.; Sheth, Jagdish N., 1938-; Jain, Varsha (London ; New York : Routledge, Taylor & Francis Group, 2025)
Customer Relationship Management in the Digital Age charts the concepts, strategies, benefits and technologies of CRM in an evolving and increasingly digital business landscape. It empowers readers with the skills to use CRM to forge enduring customer connections, optimize experiences and drive loyalty across diverse industries and markets. Building upon existing literature, this guide offers a holistic approach that bridges theory and practice, making complex CRM concepts accessible to a wide audience. It integrates the latest technological advances, market trends and customer-centric initiatives, providing a comprehensive view of CRM’s role in an increasingly customer-driven era. Pedagogical features include case studies, practical strategies and real-world examples, as well as chapter summaries and discussion questions to guide the reader through the key learning points of each chapter.
Kniha představuje ucelený průvodce moderním řízením vztahů se zákazníky v době rychlé digitalizace podnikání. Autoři vysvětlují klíčové koncepty a strategie CRM, ukazují přínosy zákaznicky orientovaného přístupu a představují nejnovější technologie, které umožňují budovat dlouhodobé vztahy, zvyšovat loajalitu a zlepšovat zákaznickou zkušenost napříč odvětvími. Publikace propojuje teorii s praxí prostřednictvím případových studií, praktických nástrojů a příkladů z reálného podnikatelského prostředí. Díky přehledné struktuře, shrnutím kapitol a otázkám k diskuzi je vhodná pro studenty, manažery i profesionály, kteří chtějí porozumět roli CRM v současné digitální ekonomice.
Obsahuje bibliografické odkazy a rejstřík
Keywords: řízení vztahů se zákazníky; řízení zákaznické zkušenosti; strategický marketing; doprovodné služby; digitální transformace; případové studie; customer relationship management; customer experience management; strategic marketing; customer services; digital transformation; case studies